Dynamic Power Quality Compensator with an Adaptive Shunt Hybrid Filter - Sindhu M R; Aneesh P; Manjula G Nair; T N P Nambiar (Institute of Advanced Engineering and Science, 2014)
Major portion of nonlinear loads in industries are contributed by variable speed drives because of their desirable features such as energy saving, smooth control, flexible operation and fast response. These electric drives introduce large amount of current and voltage harmonic distortions at the point of common coupling. These distortions are propagated throughout the system and affect all other loads connected in the system. Hence these distortions are to be mitigated with suitable harmonic filters installed near to the respective load terminals. This paper presents an effective ANN based digital controller for shunt hybrid harmonic filter to provide instantaneous harmonic and reactive compensation. The performance of the adaptive shunt hybrid filter is verified by simulation and experimental studies under steady state and dynamic conditions. The results show that it is an effective, flexible and low rated hybrid filter configuration.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.6319